The advertisement role of major urinary proteins in mice - Stopka, Pavel; Janotova, Katerina; Heyrovsky, David (Physiology & behavior, 2007)
The variation of expression of major urinary proteins was studied in laboratory mice to further the understanding of the role of these proteins in social and reproductive contexts. Mouse major urinary proteins (MUPs) are known to carry volatile substances and protect them during their passage from the liver, through the kidneys into the urine. However, most studies on the role of MUPs were carried out on males. Using densitometry analysis of total MUP concentration in the urine, our present study clearly demonstrates that (i) individuals of both sex up-regulate MUPs during social contact, and that (ii) females use these proteins to advertise their reproductive state by varying the concentration of MUPs during the oestrous cycle. As the concentration of MUPs was normalized by the concentration of creatinine -- a marker of glomerular filtration -- the corrected concentration of MUPs represents instantaneous expression on the level of proteins. Cross-correlation analysis between oestrus quantification and MUP expression revealed that the oestrous curve is delayed by 1 day behind the MUP curve so that the expression of MUPs is up-regulated immediately at the beginning of oestrus. To conclude, the regulation of pheromone-carrying MUPs is directly linked to reproduction and, thus, enables female honest signalling.
Keywords: Smell; Sex Factors; upregulace; komunikace zvířat; feromony; moč; proteiny; Up-Regulation; Proteins; Female; zvířata; myši; myši inbrední C57BL; Mice; sexuální faktory; Estrous Cycle; čich; Pheromones; Urine; ženské pohlaví; Male; Mice, Inbred C57BL; Animal Communication; estrální cyklus; Animals; mužské pohlaví